The Comparison of Free Cell and Immobilization Cell Fermentation on Bioethanol Production from Sorghum Stem by SSF and SHF Method - Permanasari, Ayu Ratna; Syamfitri, Arum; Maharani, Devina; Setyaningrum, Sinta; Wibisono, Wahyu (Politeknik Negeri Malang, 2024)
Bioethanol is a new and renewable energy source that can be produced from plants or crops containing sugars, starch, and lignocellulose. Sorghum stem contain a significant amount of sugar and lignocellulose. This study utilized sorghum stem in bioethanol production using Separated Hydrolysis and Fermentation (SHF) and Simultaneous Saccharification and Fermentation (SSF) methods. These two processes are generally used in the prouction of bioethanol with raw materials containing lignocellulose. However, raw materials derived from sweet sorghum stems has not been widely used in the previous studies. This study aimed to determine the effect of fermentation using free cell and cell immobilization techniques on various pH, as well as to identify the most optimal fermentation method (SHF or SSF) for producing the highest ethanol content in sorghum stem fermentation. The fermentation was conducted at pH levels of 3, 4, and 5. Sorghum stem were processed into powder and followed by delingnification process by 3% of NaOH solution to degrade the lignin content. The hydrolysis process of sorghum stem used cellulase enzymes as the biocatalyst. Fermentation was carried out using Saacharomyce in term of dry yeast for 72 h. The results showed that the increasing within the range pH of 3-5 will increase the ethanol concentration. Freecell technique gave the better result over the immobilized. The best result reached out the ethanol concentration of 13.04 % by the SSF.